2009
DOI: 10.1016/j.juro.2009.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Versus Computerized Tomography for Evaluating Urolithiasis

Abstract: Although computerized tomography is more sensitive for detecting urolithiasis than ultrasound, the difference in usefulness between the 2 radiological tests may not be clinically significant. Given concerns for the potentially harmful cumulative long-term effect of radiation, ultrasound should be considered the first imaging test in children with suspected urolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 21 publications
3
54
0
7
Order By: Relevance
“…In our study, the diagnostic accuracy of US was similar to that reported in the literature [3,12]. However, US fault to show small-sized renal stones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, the diagnostic accuracy of US was similar to that reported in the literature [3,12]. However, US fault to show small-sized renal stones.…”
Section: Discussionsupporting
confidence: 91%
“…US is the first preferred imaging modality. In addition, LDCT is an important method that could be used when US is not sufficient.In our study, the diagnostic accuracy of US was similar to that reported in the literature [3,12]. However, US fault to show small-sized renal stones.…”
supporting
confidence: 91%
“…The rationale for using ultrasound as the initial screening modality for children with suspected nephrolithiasis is that ultrasound accurately localizes most clinically important stones in children 17,18 and CT can be reserved for children with a nondiagnostic ultrasound for whom the clinical suspicion for stones remains high. Passerotti et al 18 observed that the sensitivity and specificity of ultrasound for 50 children with suspected nephrolithiasis were 70% and 100%, respectively, when compared with CT. Of the stones not visualized on ultrasound, 25% were in the ureter and the remainder were nonobstructive stones in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of pediatric patients will present with stones in an idiopathic manner, but 924% will have an associated secondary cause such as congenital urinary tract anomaly, metabolic deficiency, or neurologic disease [Alpay et al 2009;Kalorin et al 2009;Dursun et al 2008;Kit et al 2008;VanDervoort et al 2007;Sternberg et al 2005;Alon et al 2004]. Overall, approximately 5060% of patients have stones located in the kidney at the time of diagnosis [Passerotti et al 2009;Palmer et al 2005;Sternberg et al 2005;Kroovand, 1997]. With increasing age, though, this ratio is reversed, and in older children, the majority of stones can be found within the ureter [Kalorin et al 2009;Pietrow et al 2002].…”
Section: Pediatric Urolithiasismentioning
confidence: 99%